2017
DOI: 10.1080/03670244.2017.1406853
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Home Meal Preparation and Fast-Food Sources Use among Low-Income Urban African American Adults

Abstract: This study aimed to assess the factors associated with home meal preparation (HMP) and fast-food sources use (FFS) frequencies of low-income African-American adults and their healthy food beliefs and attitudes, food-related psychosocial factors, food acquisition patterns, food sources use, and BMI. We used cross-sectional data from 295 adults living in Baltimore, USA. HMP was inversely associated with FFS, which had lower odds of HMP ≥1 time/day and higher BMI scores. HMP was positively associated with positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
2
16
0
1
Order By: Relevance
“…Thus, an association with lower consumption of empty calories and cooking suggests a healthier behavioral pattern of those adults who cook more. This is similar to findings from Wolfson and Bleich [7] that cooking frequency is associated with lower intake of fast food, and by that of Gustat, et al [13] who found that Non-Hispanic Blacks living in New Orleans had lower consumption of purchased foods when home cooking was present at least daily.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, an association with lower consumption of empty calories and cooking suggests a healthier behavioral pattern of those adults who cook more. This is similar to findings from Wolfson and Bleich [7] that cooking frequency is associated with lower intake of fast food, and by that of Gustat, et al [13] who found that Non-Hispanic Blacks living in New Orleans had lower consumption of purchased foods when home cooking was present at least daily.…”
Section: Discussionsupporting
confidence: 89%
“…Three, cooking behavior choices reflect not only what is available based on SES situations, but also household level and individual attitudes related to ability, skills, and self-efficacy. For example, Garcia, et al [13] in a cross-sectional survey of Non-Hispanic Black adults in Baltimore found self-efficacy for healthy foods was positively associated with cooking frequency. Our finding of a significant association of high PDQ and cooking frequency is consistent with the role of psychosocial factors and cooking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own group’s NHANES (National Health and Nutrition Examination Survey) analysis of cooking frequency among African-Americans found that employment, income, and self-perceived diet quality were significant determinants of home cooking frequency [ 2 ]. Cross-sectional studies from an African-American population in a Baltimore food desert show that self-efficacy and beliefs are also contributors and are positively associated with cooking frequency and type of home cooking method [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%